The Influence of Snowball Throwing and Teams Games Tournament Cooperative Learning Models on the Learning Outcomes of Elementary School Students - Sri Murtini; Murtono Murtono; Sri Utaminingsih (Journal Prakarsa Paedagogia, 2022)
The purpose of this study is to analyze the effect of the Snowball Throwing and Teams Games Tournament learning models on learning outcomes and explain the differences between the Snowball Throwing learning model and the Teams Games Tournament learning outcomes on heat transfer science subjects in elementary schools. The results of the research 1) there is an influence of the snowball throwing learning model on the science learning outcomes of heat transfer material for Students of 1st Kuwu State Elementary School, Dempet, Demak based on the value of Sig. (2-tailed) 0.000 < 0.05, or t-count 9.657 > t-table 2.06390. The magnitude of the influence is 15.80. 2) There is an influence of the Team Games Tournament (TGT) learning model on the science learning outcomes of heat transfer material for fifth-grade Students of 4th Dempet State Elementary School, Dempet, Demak based on the value of Sig. (2-tailed) obtained 0.000 < 0.05, or t-count 11.932 > t-table 2.05183 while the magnitude of the effect given is 23.99. 3) There is a difference in the influences between the snowball throwing learning model and the team games tournament (TGT) on the improvement of science learning outcomes for fifth-grade Students heat transfer material in elementary schools. It can be concluded that the experimental 2nd experimental class research using the Team Games Tournament (TGT) learning model increased learning outcomes higher than the 1st experimental class research which used the snowball throwing learning modelÂ